Implications of COVID-19 pandemic on the epidemiological behavior of dengue cases reported on the municipality of Cascavel-PR: A cross-sectional analisys (Research, Society and Development, 2024)
Dengue is a disease whose main symptoms are high fever, headache, myalgia, malaise, sweating and, in more serious cases, severe bleeding. Its transmission occurs through the bite of the Aedes aegypti mosquito in four types of strains (DENV-1, DENV-2, DENV-3 and DENV-4). Tropical countries are those that suffer most from the dengue virus, because the climatic conditions in these countries help to prevent the Aedes aegypti mosquito. In classic cases, treatment is carried out with analgesics, antipyretics and hydration. If it develops into dengue hemorrhagic fever, the patient must be observed and identify the first signs of shock. This article aimed to elucidate the impacts of the new Coronavirus Pandemic on Dengue public health processes in the municipality of Cascavel-PR. This is an observational, cross-sectional and retrospective study, where data from the Diseases of Notification (SINAN) about Dengue in the municipality of Cascavel-PR, considering several variables in the pre-pandemic and trans-pandemic periods. Through the results it was possible to observe that in the years 2020 and 2022 there was an endemic of the disease in the municipal sphere, in addition at the beginning of the Pandemic (2020) the number of cases reported with blank variables increased, in addition there were prominent clinical diagnoses - epidemiological, this was due to the failure to carry out elective laboratory tests during the pandemic period.